Capturing the gaze in film: Feminist critiques of Jewish and Islamic orthodoxy in Israel and Iran - Shenker, Yael (Critical research on religion, 2018)
This article addresses issues of body and sexuality exposed by documentary films about orthodox Jewish women in Israel and traditional Islamic women in Iran, directed by Anat Yuta Zuria and Ziba Mir-Hosseini (with Kim Longinotto), respectively. These two groups of religious women are faced with some similar circumstances. The directors of these films use their cameras to expose not only the male gaze, but sometimes they also turn their cameras back on the men who perpetuate and benefit from religious legal systems that subjugate these women. The camera thus is not merely a documentary tool but also a political tool revealing what is hidden in the inner sanctum and redeeming it from the "private sphere." This comparison highlights the potential of Jewish feminism in Israel; it challenges it to work in alliance with Islamic women who live either as citizens in Israel or as non-citizens in the occupied territories.